2008
DOI: 10.1016/j.physa.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and memory effect in volatility return interval of the Chinese stock market

Abstract: We investigate the probability distribution of the volatility return intervals τ for the Chinese stock market. We rescale both the probability distribution P q (τ ) and the volatility return intervals τ as P q (τ ) = 1/τ f (τ /τ ) to obtain a uniform scaling curve for different threshold value q. The scaling curve can be well fitted by the stretched exponential function f (x) ∼ e −αx γ , which suggests memory exists in τ . To demonstrate the memory effect, we investigate the conditional probability distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
4
23
1
Order By: Relevance
“…It has been found that the recurrence interval distribution above a fixed threshold has a power-law tail for the daily volatilities in Japanese market [13,26], the minute-by-minute volatilities in Korean market [27] and Italian market [28], the daily returns in US stock markets [3,16,17], the minute-by-minute returns in Chinese markets [18], and the minute-by-minute trading volume in US markets [25] and Chinese markets [24]. A number of studies ranging from daily to high-frequency data and from developed to emerging markets [14,[29][30][31][32][33][34][35][36], have also reported that the distribution of the recurrence intervals of financial volatility is a stretched exponential. Reference [22] reports that in Chinese markets the recurrence time between returns above a given positive threshold or below a negative threshold for the index spot and futures fits a stretched exponential distribution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the recurrence interval distribution above a fixed threshold has a power-law tail for the daily volatilities in Japanese market [13,26], the minute-by-minute volatilities in Korean market [27] and Italian market [28], the daily returns in US stock markets [3,16,17], the minute-by-minute returns in Chinese markets [18], and the minute-by-minute trading volume in US markets [25] and Chinese markets [24]. A number of studies ranging from daily to high-frequency data and from developed to emerging markets [14,[29][30][31][32][33][34][35][36], have also reported that the distribution of the recurrence intervals of financial volatility is a stretched exponential. Reference [22] reports that in Chinese markets the recurrence time between returns above a given positive threshold or below a negative threshold for the index spot and futures fits a stretched exponential distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a lot of physicists devoted to the study of financial dynamics in the past two decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14], and some stylized facts have been revealed from the statistical physics perspective. Scaling behavior of the return and return interval distributions has been observed for different markets [1][2][3][4][15][16][17][18]. Volatility clustering is found to be universal for most markets [3,19].…”
Section: Introductionmentioning
confidence: 86%
“…From a volume volatility time series, we may extract the recurrence intervals τ between consecutive volatilities above a threshold q, and construct a series of the recurrence intervals {τ (q)} [26,27,28,29]. The threshold q is measured in unit of the standard deviation of the volume volatility.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…The analysis of the recurrence interval may deepen the understanding of the dynamic behavior in financial markets [21,25]. Recently, statistical properties of the recurrence intervals of volume volatilities and price volatilities have been studied [26,27,28,29]. We present a comparative study on the recurrence interval distributions of the four stock markets.…”
Section: Introductionmentioning
confidence: 99%